-6k-3k=27

Simple and best practice solution for -6k-3k=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6k-3k=27 equation:


Simplifying
-6k + -3k = 27

Combine like terms: -6k + -3k = -9k
-9k = 27

Solving
-9k = 27

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Divide each side by '-9'.
k = -3

Simplifying
k = -3

See similar equations:

| 0(x)=12x+1 | | b1/2 | | 5x2/7= | | 9(4-5x)+9x= | | -2(x)=12x+1 | | -91.608=-4.4(2.4x+5.7) | | -5m+4=11-4m | | -3/2x-2/3(47/10x-8/3) | | 3(x)=12x+1 | | 7a+7(4a-5)= | | F+6=-7 | | x^5-33x^3+200x=0 | | 110-56/x | | -4n+y+2n=1 | | 5+2(x-3)=3 | | 1.5c-18=35 | | 3x-4x-10=4 | | 7x+12=3x+28 | | 3x+2x+x=189 | | 5x+27=312 | | A-5A=100 | | -6x+n=12 | | d/-3=-6 | | 29x-32=4x+589 | | 4=8+b | | 2x+8=2-x+8 | | -22(b-982)=-308 | | 25.00+.10x=45.00 | | 82.8=9(m+2.3) | | X+8+3x-6=180 | | 3x-6+x+8=90 | | (i-3)+6i-3(8-i)=0 |

Equations solver categories